Modernism after the death of God : Christianity, fragmentation, and unification - Kern, Stephen (New York, NY ; Abingdon, Oxon : Routledge, an imprint of the Taylor & Francis Group, 2017)
"Modernism After the Death of God: Christianity, Fragmentation, and Unification explores the writing and philosophies of some of the most popular modernist figures studied today. This ground-breaking work, is an interpretation of the life and work of Friedrich Nietzsche, James Joyce, Sigmund Freud, D. H. Lawrence, Andre Gide, Martin Heidegger and Virginia Woolf that shows how each related to and drifted from religion in large part because they believed that Christian sexual morality had damaged or threatened to damage their love life" --
Introduction: from Christian unity to modernist unification -- Friedrich Nietzsche: greatness, meaning, and authenticity -- James Joyce: wholeness, harmony, and radiance -- Sigmund Freud: psychoanalysis and psychosynthesis -- D. H. Lawrence: spontaneous-creative fullness of being -- Andre Gide: wholly available to life and love -- Martin Heidegger: pursuing the question of being -- Virginia Woolf: creating shape out of chaos -- Conclusion: a modernist ideal type.
Includes bibliographical references and index.
ENH
Parama
Keywords: 1800-1999; Modernism (Literature); Christianity and literature -- Europe; Sex (Psychology) in literature; European literature -- 20th century -- History and criticism; European literature -- 19th century -- History and criticism; Christianity and literature; European literature; Modernism (Literature); Sex (Psychology) in literature; Europe